Empowering the search for pleasure, health and well‐being outside heteronormative definitions: The role of evaluation in shaping structurally sensitive programming for 2SGBTQ+ men who Party and Play in Ontario. Issue 175 (21st October 2022) - Ismail, Yasser; Griffiths, Dane; Bond‐Gorr, Jordan
Abstract: Sexualized drug use, also known as Party and Play (PnP, chemsex) is a phenomenon that is increasingly pervasive among 2SGBTQ+ communities in Canada and has been epidemiologically linked to increased risk of HIV and other sexually transmitted and blood‐borne illnesses (STBBI). The phenomenon is highly stigmatized even within 2SGBTQ+ communities, perpetuating discrimination against individuals who PnP. Consequently, such individuals often remain invisible to formal care systems. Even as public health efforts seek to reduce the harms associated with PnP, narrowly epidemiological understandings of the phenomenon without understanding it from the perspectives of those with living experience of it, and—without attention to how historical, socio‐structural, and cultural factors shape the phenomenon—contribute to the stigmatization, disempowerment, and marginalization of people who PnP from healthcare access. In this chapter, we describe how an evaluation‐driven program design process grounded in the transformative evaluation paradigm and the principles of LGBTQ+ evaluation supported a paradigm shift for one public health agency in how they re‐conceptualized a more empowering approach for engaging people who PnP in dignified, meaningful care.